Dengue fever complicated with Guillain-Barré syndrome: a case report and review of the literature - Chamara Dalugama; John Shelton; Mahendra Ekanayake; Indika Bandara Gawarammana (Journal of Medical Case Reports, 2018)
Abstract Background Dengue is an arboviral infection classically presenting with fever, arthralgia, headache, and rashes. It is hyperendemic in Sri Lanka and has a major impact on health. Neurological complications of dengue fever are rare but have been reported in the literature. Case presentation A 60-year-old Sri Lankan man presented with a history of fever, arthralgia, and generalized malaise of 2 days duration. A diagnosis of dengue was confirmed with leukopenia, thrombocytopenia, and positive NS1 antigen done on day 2 without evidence of hemoconcentration. On admission, our patient had weakness of the bilateral lower limbs, which progressed in an ascending pattern involving both upper limbs and neck muscles, requiring assisted ventilation. Electromyography confirmed a demyelinating polyneuropathy and cerebrospinal fluid showed albumincytological dissociation. He was treated with intravenous immunoglobulins and made an uneventful recovery. Subsequently, his immunoglobulin M test result for dengue virus was positive. Conclusions Guillain-Barré syndrome is a rare but possible neurological sequel following dengue fever. In regions where dengue is hyperendemic, screening for dengue illness may be important in patients presenting with acute flaccid paralysis.